Assessment of constellation designs for earth observation: Application to the TROPICS mission. (August 2019) - Buzzi, Pau Garcia; Selva, Daniel; Hitomi, Nozomi; Blackwell, William J.
Abstract: The orbit and constellation design process for Earth observation missions is complex and it involves trades between mission lifetime, instrument performance, coverage, cost, and robustness among others. This paper describes an orbit and constellation design study conducted during Pre-Phase A and Phase A for the NASA-funded Time-Resolved Observations of Precipitation structure and storm Intensity with a Constellation of SmallSats (TROPICS) mission. Thousands of potential constellations were enumerated, simulated using an open-source astrodynamics library, and compared with one another across multiple dimensions, focusing on cost and coverage considerations. The robustness of different constellations to various hypothetical operational failures (e.g., loss of one satellite or one launch) was systematically assessed. A deployment strategy based on differential drag was proposed and analyzed for selected constellations. Finally, the orbital lifetime of various architectures was also studied with respect to NASA's 25-year de-orbiting recommendation. The contributions of this work include: (1) an exhaustive analysis of figures of merit commonly used in Earth observation orbit design; (2) A methodology to assess robustness of constellations based on a brute-force disjoint scenario simulation approach; (3) Results and recommendations from the mission analysis process for the TROPICS mission. Highlights: We describe a constellation design study performed for the NASA TROPICS mission. We provide general constellation design guidelines for Earth observation missions. We include a discussion of the most common metrics used in constellation design. We analyze the sensitivity of coverage metrics to constellation design decisions. We describe a method to quantify constellation robustness with respect to coverage.